2012
DOI: 10.1021/la301610a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture: Construction of Self-Assembled Organophosphonate Duplexes and Their Electrochemical Characterization

Abstract: Self-assembled monolayers of phosphonates (SAMPs) of 11-hydroxyundecylphosphonic acid, 2,6-diphosphonoanthracene, 9,10-diphenyl-2,6-diphosphonoanthracene, and 10,10'-diphosphono-9,9'-bianthracene and a novel self-assembled organophosphonate duplex ensemble were synthesized on nanometer-thick SiO(2)-coated, highly doped silicon electrodes. The duplex ensemble was synthesized by first treating the SAMP prepared from an aromatic diphosphonic acid to form a titanium complex-terminated one; this was followed by add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…In particular, SAMs of aliphatic organophosphonic acids on metal and semiconductor oxide surfaces are of interest due to their ability to tune the electronic properties of the substrate and to their relative robustness under ambient conditions [2], [3]. α,ω-Bisphosphonic acids (bisPA), which feature a distal phosphonic acid terminating group, have found application for growing three-dimensional structures such as stacked duplex layers [4], [5]. We recently demonstrated that SAMs of aliphatic bisPAs can act as strong tunneling current attenuators -an appealing property for applications as gate dielectric modifiers in organic transistor devices [6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, SAMs of aliphatic organophosphonic acids on metal and semiconductor oxide surfaces are of interest due to their ability to tune the electronic properties of the substrate and to their relative robustness under ambient conditions [2], [3]. α,ω-Bisphosphonic acids (bisPA), which feature a distal phosphonic acid terminating group, have found application for growing three-dimensional structures such as stacked duplex layers [4], [5]. We recently demonstrated that SAMs of aliphatic bisPAs can act as strong tunneling current attenuators -an appealing property for applications as gate dielectric modifiers in organic transistor devices [6].…”
Section: Introductionmentioning
confidence: 99%
“…The Au(111) surface was modeled using five atomic layers, the bottom two being kept fixed and the remaining three layers being mobile. Each layer comprised 36 atoms with lateral dimensions of 15 the alkanethiols are bounded to the surface through the S atom on-top binding-sites, and form a densely packed layer arranged into a (…”
Section: Simulation Detailsmentioning
confidence: 99%
“…15 A detailed knowledge of the structure of the molecule metal interface is needed to understand the growth mechanism 16 and the electrostatic properties 17 of this kind of materials. However, the structural features of thiols absorbed on the gold(111) crystal surface are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, organophosphonates are preferable to siloxanes for modifying inorganic surfaces ( e . g ., SiO 2 ), thanks to their superior monolayer properties . Indeed, aromatic organophosphonate monolayers (SAMPs) find applications in functionalizing surfaces because of their high stability and excellent passivating properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, organophosphonates are preferable to siloxanes for modifying inorganic surfaces (e.g., SiO 2 ), thanks to their superior monolayer properties. [3][4][5][6][7][8][9][10] Indeed, aromatic organophosphonate monolayers (SAMPs) find applications in functionalizing surfaces because of their high stability and excellent passivating properties. High-quality organophosphonate monolayers have shown excellent dielectric and interfacial properties in high-performance OFETs.…”
Section: Introductionmentioning
confidence: 99%